Development and Validation of Chemometric Assisted UV Methods for the Simultaneous Determination of Ambroxol Hydrochloride, Terbutaline Sulphate and Guaiphenesin in Pharmaceutical Dosage Form - Palur, Keerthisikha; Archakam, Sreenivasa Charan; Koganti, Bharathi (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim: The present study aimed to develop and validate chemometric assisted UV spectrophotometric methods for the simultaneous determination of ambroxol hydrochloride (ABH), terbutaline sulphate (TES) and guaiphenesin (GPN) in their combined dosage form. Materials and Methods: The two chemometric models applied for the UV spectroscopic data were principal component regression (PCR) and partial least squares regression (PLS). Standard mixture solutions containing different ratios of ABH, TES and GPN in the calibration ranges of 5-30 μg/mL, 25-125 μg/mL and 15-75 μg/mL respectively were prepared and their UV absorption spectra was recorded. Calibration data set and validation data set comprising of thirteen and nine standard mixture solutions respectively were constructed and computations were made using UNSCRAMBLER X version 10.0 software for both the models in the wavelength region of 240-310 nm. Results: The results obtained by the optimized chemometric calibration models depicted the accuracy of the models and the assay results of PCR and PLS for the quantification of ABH, TES and GPN in the syrup dosage form were found to be within the acceptance criteria. Conclusion: The developed PCR and PLS models were found to simple, economical, accurate and do not require any separation process.
Keywords: Chemometric models; Principal component regression; Partial least squares regression; Ambroxol hydrochloride; Terbutaline sulphate; Guaiphenesin